Death-Associated Protein Kinase 1 as a Promising Drug Target in Cancer and Alzheimer’s Disease - Chen, Dongmei; Zhou, Xiao Z.; Lee, Tae H. (Recent Patents on Anti-Cancer Drug Discovery, 2019)
Background: Death-Associated Protein Kinase 1 (DAPK1) plays an important role in apoptosis, tumor suppression and neurodegeneration including Alzheimer’s Disease (AD). Objective: This review will describe the diverse roles of DAPK1 in the development of cancer and AD, and the current status of drug development targeting DAPK1-based therapies. Methods: Reports of DAPK1 regulation, function and substrates were analyzed using genetic DAPK1 manipulation and chemical DAPK1 modulators. Results: DAPK1 expression and activity are deregulated in cancer and AD. It is down-regulated and/or inactivated by multiple mechanisms in many human cancers, and elicits a protective effect to counteract numerous death stimuli in cancer, including activation of the master regulator Pin1. Moreover, loss of DAPK1 expression has correlated strongly with tumor recurrence and metastasis, suggesting that lack of sufficient functional DAPK1 might contribute to cancer. In contrast, DAPK1 is highly expressed in the brains of most human AD patients and has been identified as one of the genetic factors affecting susceptibility to late-onset AD. The absence of DAPK1 promotes efficient learning and better memory in mice and prevents the development of AD by acting on many key proteins including Pin1 and its downstream targets tau and APP. Recent patents show that DAPK1 modulation might be used to treat both cancer and AD. Conclusion: DAPK1 plays a critical role in diverse physiological processes and importantly, its deregulation is implicated in the pathogenesis of either cancer or AD. Therefore, manipulating DAPK1 activity and/or expression may be a promising therapeutic option for cancer or AD.
Keywords: apoptosis